PEMBERIAN PUPUK KANDANG SAPI DAN GROWMORE 12-45-10 PADA PERTUMBUHAN TANAMAN BUAH NAGA (Hylocereus costaricensis) - Novra Viloga; Hercules Gultom; T Edy Sabli (UIR Press, 2013)
The aim of this research was to know the effect of organic fertilizer and Growmore 12-45-10 application on Naga Growth. The experiment used the randomized block design with two factors in three blocks. The first factor was application of organic fertilizer (S), which consisted of S0 (3.0 kg/pole), S1 (4.5 kg/pole), S2 (6.0 kg/pole), and S3 (7.5 kg/pole). The second factor was application of Grownore (G) which consisted of G0 (1.5 g/lt), G1 (2.0 g/lt), G2 (2.5 g/lt) and G3 (3.0 g/lt). The observed parameter was height growth, length of shoot growth, the number of shoot growth, and spiraling shoot growth. The result showed that interaction of application of manure and Growmore had no effect on growth of dragon fruit. Organic fertilizer alone had a significant effect on height growth, length of shoot growth, the number of shoot growth, and spiraling shoot growth with the best treatment of 7.5 kg/pole. The application of various Growmore concentrations alone showed a significant effect on height of plant, length of shoot growth, the number of shoot growth, and spiraling shoot growth with the best treatment of 3.0 g/lt of water.